Soil Gas Diffusivity Controls N2O and N2 Emissions and their Ratio. Issue 3 (24th June 2016) - Balaine, Nimlesh; Clough, Tim J.; Beare, Mike H.; Thomas, Steve M; Meenken, Esther D.
Abstract : Core Ideas: Relative gas diffusivity controls both N2 O and N2 emissions. Relative gas diffusivity integrates the effects of soil bulk density and matric potential. Nitrogen use efficiency is likely to be driven by soil physics. Knowledge of soil biological and physical interactions with respect to N2 O and N2 fluxes is essential to ensure that agricultural land management is environmentally and economically sustainable. This study determined how varying soil relative gas diffusivity ( D p / D o ) affected cumulative N2 O and N2 fluxes under simulated ruminant urinary‐N deposition. Using repacked soil cores, the effects of varying soil bulk density (ρb ; from 1.1 to 1.5 Mg m −3 ) and soil matric potential (ψ; −10 to −0.2 kPa) on D p / D o were examined in a Templeton silt loam soil (Udic Haplustept) following the application of simulated ruminant urine (700 kg N ha −1 ). Fluxes of N2 O and N2, soil inorganic N, pH, and dissolved organic C (DOC) dynamics were monitored over 35 d. Soil D p / D o declined as soil bulk density and soil moisture increased. Soil N2 O emissions increased exponentially as D p / D o decreased until D p / D o equaled 0.005, where upon N2 O fluxes decreased rapidly due to complete denitrification, such that N2 fluxes reached a maximum of 60% of N applied at a D p / D o of <0.005. Regression analysis showed that D p / D o was better able to explain the variation in N2 O and N2 fluxes than water‐filled pore space (WFPS) because it accounted for the interaction of soil ρb and ψ. This study demonstrates that soil D p / D o can explain cumulative N2 O and N2 emissions from agricultural soils. Under grazed pasture systems, potential exists to reduce the emissions of the greenhouse gas N2 O and significant economic losses of N as N2 if soil management and irrigation can be maintained to maximize D p / D o .